PENERAPAN MODEL PEMBELAJARAN RMS (READING, MIND MAPPING, AND SHARING) PADA MATERI SISTEM EKSKRESI MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI - Hamdiah, Resky; Nur, Muhammad; Rahim, Sahriah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research is classroom action research which is motivated by the low learning outcomes of students in the learning process in class. What influences low student learning outcomes is the lack of student activity in the learning process. Plus the learning process uses a monotonous lecture method. This research aims to find out whether applying the RMS (Reading, Mind Mapping, and Sharing) learning model to the Human Excretory System material can improve the learning outcomes of class XI MIPA 5 UPT SMAN 3 Wajo students. The subjects of this research were all students of class XI MIPA 5 UPT SMAN 3 Wajo for the 2022/2023 academic year, totaling 31 students. This research was carried out in 2 cycles, each cycle held 3 meetings. The learning process for each meeting is designed by applying the RMS (Reading, Mind Mapping, and Sharing) learning model. The instruments used were student activity observation sheets and student learning outcomes tests in the form of multiple choices. At the end of each cycle, a learning outcomes test is carried out. Based on the research results, it shows that there is an increase in student learning activities from cycle I to cycle II. In cycle I the percentages were 29.5%, 37.6%, and 46.2%. Meanwhile, in cycle II the percentages were 58.6%, 67.2%, and 78.4%. This was followed by an increase in student learning outcomes from cycle I with a percentage of 41.9% to 87.1% in cycle II. From these results, it can be concluded that implementing the RMS (Reading, Mind Mapping, Sharing) learning model, can improve student learning outcomes in Biology lessons in Class XI MIPA 5 UPT SMAN 3 Wajo.